O'Reilly Velocity Conference 2019, Berlin, Germany. (O'Reilly Media, 2019)
"O'Reilly Velocity Conferences are devoted to providing its international audience of SREs, app developers, DevOps practitioners, systems architects, CTOs, and CIOs with the most on-point training and information possible on how to build and maintain large-scale cloud native systems. Velocity Berlin 2019 stayed true to this formula. It gathered some of the world's top cloud practitioners to share their expertise and insights on key concepts like Kubernetes, site reliability engineering, observability, and performance. Stay ahead of your competition, get this video compilation, and enjoy a front-row seat to all of the best that Velocity Berlin 2019 had to offer."--Resource description page